Pengukuran Keimanan: Perspektif Psikologi - Shodiq, Shodiq (Nadwa: Jurnal Pendidikan Islam, 2014)
Faith material is the basic and essential part of the learning goals in the context of strengthening the students' personalities, especially in teaching religious education. As the purpose of learning, faith must also be evaluated and measured so that it is known to what extent the learning objectives have beenachieved. The problem is how to evaluate and measure one's faith? Only Allah can measure and determine the degree of one's faith, donâ€™t you? How to measure the faith will be discussed in this paper. This study would be useful for teachers in detecting an increase or decrease of the quality of students' faith in accordance with the indicators that have been determined.Â AbstrakPada konteks penguatan kepribadian siswa, materi keimanan dan ketakwaan merupakan bagian pokok dan penting dalam tujuan pembelajaran bagi siswa, khususnya pembelajaran pendidikan agama, tidak terkecuali Pendidikan AgamaIslam (PAI). Sebagai tujuan pembelajaran, keimanan juga harus dapat dievaluasi dan diukur sehingga dapat diketahui sejauh mana tujuan pembelajaran tersebut telah tercapai. Persoalannya adalah bagaimana mengevaluasi dan mengukurkeimanan seseorang? Tidakkah yang berhak mengukur dan menentukan derajat keimanan seseorang hanyalah Allah, Tuhan Yang Maha Tahu? Bagaimana mengukur keimanan inilah yang hendak dibahas dalam jurnal ini. Sehingga denganadanya kajian tentang penguatan keimanan secara psikologis, akan bermanfaat bagi guru dalam mendeteksi peningkatan atau penurunan kualitas keimanan anak didik sesuai indikator keimanan yang sudah ditentukan.